Pemenuhan dan Perlindungan Hak-hak Prosedural Korban Terorisme atas Victim Impact Statements (VIS) dalam Sistem Peradilan Pidana - Susetyo, Heru (Universitas Sultan Ageng Tirtayasa, 2024)
Victims and perpetrators of crime still experience different treatment in Indonesia. These differences are expressed in statutory regulations and national law enforcement practices. The same is true for victims of terrorism. Attention to suspects or perpetrators of terrorism is much greater than to victims. Moreover, in many cases of terrorism, the perpetrator and victim do not know each other. The rights of victims internationally are written down in various international legal products. There are two large groups of victims' rights: procedural and service rights. This article discusses the procedural rights of victims of terrorism, specifically in the aspect of fulfilling and protecting victims' impact statements. The research approach is qualitative, and data collection is carried out by reviewing literature and studying legislation by comparing the fulfillment and protection of the rights of victims' impact statements in other countries. The findings from this research are that the rights of victims of terrorism regarding victim impact statements have not been specifically regulated in Indonesian law. This is reflected in the trial process and in the words of surviving victims of terrorism. Then, the suggestion from these findings is that the need for justice for victims and their families related to procedural rights, specifically the right to victims' impact statements, needs to be regulated explicitly in Indonesian law and applied in everyday criminal justice practice.